Quality Management Of Arabic Language Learning At MAN 3 Merangin - Hadziq, Muhammad Fadhil; Mubarok, Khusnul; Fithtriyah, Aidah; Algatnaini, Raed Awadh Saeed; Fikri, Shofil (Universitas Pakuan, 2025)
This study examines the quality management of Arabic language learning at MAN 3 Merangin, based on George Robert Terry's management theory. The background of this research highlights the importance of Arabic in religious education, yet learning is often suboptimal due to challenges such as low student motivation and limited learning media. This study aims to analyze the implementation of four main aspects of management: planning, organizing, actuating, and controlling, in order to improve the quality of learning. The research method uses a qualitative approach with a case study, involving interviews, observations, and documentation. The results show that in planning, teachers develop syllabi and lesson plans in accordance with the Merdeka Curriculum, using a Project-Based Learning (PBL) approach. In organizing, tasks are clearly divided between teachers and the Quality Assurance Team. Actuating of learning involves active methods such as group discussions, simulations, and projects, along with the use of innovative media to engage students. Controlling is regularly conducted by the principal and management team to ensure the quality of learning remains high. Evaluation is carried out using written, oral, and formative tests to measure students' listening, speaking, reading, and writing skills in Arabic. Overall, this quality management approach improves the learning quality and can serve as a model for other institutions.